2007
DOI: 10.1016/j.pain.2006.11.004
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of the relation between physical capacity and future low back and neck/shoulder pain

Abstract: The results of longitudinal studies reporting on the relation between physical capacity and the risk of musculoskeletal disorders have never been reviewed in a systematic way. The objective of the present systematic review is to investigate if there is evidence that low muscle strength, low muscle endurance, or reduced spinal mobility are predictors of future low back or neck/shoulder pain. Abstracts found by electronic databases were checked on several inclusion criteria. Two reviewers separately evaluated th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
85
1
10

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 116 publications
(101 citation statements)
references
References 48 publications
5
85
1
10
Order By: Relevance
“…This includes psychological factors such as health beliefs, mood, and the tendency to worry about common somatic symptoms (somatizing tendency) (9, 10); mental comorbidities (11), sleep problems (12), and pain sensitivity and/or augmented central processing of sensory information (13,14). Also, personal (eg, age, gender and physical capacity) (15) and (work-related) psychosocial factors (eg, stress, social support and job satisfaction) (16,17) are known to play a role in the occurrence of MSD. Apart from these factors, however, research into the factors associated with MSD has for a vast amount focused on work-related physical risk factors, including manual lifting, repetitive hand/arm movement (such as computer work) and awkward body postures, for the prevention of LBP (18), upper-extremity symptoms (19) and MSD in general (20), respectively.…”
Section: Van Der Beek Et Almentioning
confidence: 99%
See 1 more Smart Citation
“…This includes psychological factors such as health beliefs, mood, and the tendency to worry about common somatic symptoms (somatizing tendency) (9, 10); mental comorbidities (11), sleep problems (12), and pain sensitivity and/or augmented central processing of sensory information (13,14). Also, personal (eg, age, gender and physical capacity) (15) and (work-related) psychosocial factors (eg, stress, social support and job satisfaction) (16,17) are known to play a role in the occurrence of MSD. Apart from these factors, however, research into the factors associated with MSD has for a vast amount focused on work-related physical risk factors, including manual lifting, repetitive hand/arm movement (such as computer work) and awkward body postures, for the prevention of LBP (18), upper-extremity symptoms (19) and MSD in general (20), respectively.…”
Section: Van Der Beek Et Almentioning
confidence: 99%
“…As such, several models from various disciplines have been proposed addressing different aspects of work-related MSD prevention, for instance providing focused approaches to mechanisms for work-related risk factors and preventive interventions or implementation (table 1). Apart from work-related physical risk factors, these models address other factors that may play a role in the development of MSD, such as personal factors (eg, age, gender and physical capacity) (15) and (workrelated) psychosocial factors (eg, stress, social support and job satisfaction) (16,17). Although these models could, in theory, be compatible with one another, none of them fully covers all research disciplines that link mechanisms with interventions and implementation.…”
Section: Van Der Beek Et Almentioning
confidence: 99%
“…An imbalance between exposure to mechanical workload and the individual's physical capacity might be a risk factor of musculoskeletal disorders. However, few quality studies have evaluated these associations, and a previous review has found the literature inconclusive (52).…”
Section: Hanvold Et Almentioning
confidence: 99%
“…Physical fitness comprises several components with cardio respiratory endurance as the most important, because of its strong relations to development of chronic diseases like cardiovascular diseases, diabetes, cancer and premature death (Blair SN et al, 1989;Myers JN et al, 2002), whereas muscle strength and endurance show inconsistent relation to musculoskeletal disorders (Hamberg-van Reenen HH et al, 2007) Additional components are musculoskeletal flexibility and body composition. This report is restricted to simple methods for assessing cardio respiratory endurance, muscle strength and muscle endurance in larger populations.…”
Section: Physical Fitnessmentioning
confidence: 99%